PENGARUH KECOCOKAN ETIKA DAN KOMITMEN ORGANISASI TERHADAP TINGKAT TURNOVER MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Sri Rahayu (Jurnal Manajemen Bisnis Unbara, 2020)
The objectives of this research are: (1) to analyze and know how big the personality fit effects job satisfaction of employees empirically, (2) to analyze and know how big the organization commitment effects job satisfaction of employees empirically,(3) to analyze and know how big the personality fit effect turnover intentions of employees empirically, (4) to analyze and know how big the organization commitment effect on turnover intentions of employees empirically, and (5) to analyze and know how big the job satisfaction effect on turnover intentions of employees empirically. Forty three respondents were selected by using census sampling method; those were the ones who worked in Mahakarya Asia University of Studi Program outside the main campus Baturaja. They have been working for more or less five years. The data were collected by questionnaires and documentation. The data were analyzed by using regression analysis. The result showed that R square (R2) was 62.4% and significance level was 0.000.This result indicated that personality fit and organization commitment affected positively and significantly on job satisfaction. Therefore, the result showed that R square (R2) 53.4% and significance level was 0.000. This result indicated that personality fit and organization commitment affected negatively and significantly on turnover intentions. These findings strengthened other researchers’ finding in which personality fit and organization commitment factors had direct effects on turnover intentions and personality fit and organization commitment factors had indirect effects on turnover intentions using job satisfaction as intervening variable.